POTENSI PENGEMBANGAN PUPUK ORGANIK INSITU MENDUKUNG PERCEPATAN PENERAPAN PERTANIAN ORGANIK (Forum Penelitian Agro Ekonomi, 2013)
Organic fertilizer in-situ application is the beginning of organic farming. In-situ organic fertilizer raw materials can be obtained from straw and dung. National straw production is 30.4 million tons per year and cow’s dung production is 3.8 million tons per month. Technology for organic fertilizer production is simple, namely through stacking the straw and flipping it. Solid fertilizer organic fertilizer cost is Rp 417 per kg and that of liquid organic fertilizer is Rp 3,510 per liter. Accelerating organic farming implementation can be carried out through: (1)  use of straw, (2) sustainable cattle and livestock integration program, (3) price subsidy policy, (4) provision of organic fertilizer processing equipments, composting houses, and organic fertilizer processing units, and (5) standardization and labeling of farmers-produced organic fertilizer.
Keywords: agriculture; organic; fertilizers; pertanian; organik; pupuk